KUALITAS PAPAN PARTIKEL DARI LIMBAH TANDAN KOSONG KELAPA SAWIT DENGAN PEREKAT DAMAR - Akbar, Muhammad Rizali; Harun, Noviar; Hamzah, Farida Hanum (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Oil palm empty bunches are one of the solid wastes from the processing of fresh fruit bunches that have not been used optimally. This study aims to obtain the best concentration of resin adhesives in the manufacture of particleboard from oil palm empty fruit bunches. The research was conducted experimentally using a completely randomized design (CRD) with 5 treatments and 3 replications in order to obtain 15 experimental units with a particle size of 16 meshof oil palm empty bunches. Treatment of oil palm empty bunches with adhesive is 90%: 10%, 88%: 12%, 86%: 14%, 84%: 16%, 82%: 18%. The data obtained were analyzed statistically using Analysis of Variance (ANOVA) and Duncan New Multiple Range Test (DNMRT) at the 5% level. The results showed that the composition of the empty fruit bunches of oil palm and resin adhesive significantly affected the density, water absorption, thickness expansion, elasticity modulus, and fracture modulus, but had no significant effect on moisture content.The best treatment chosen was treatment P5 with a density value of 0.85 g/cm3, water content of 5.81%, water absorption 61%, thickness development 53.33%, modulus of elasticity 1.607.46 kgf/cm2, modulus of fracture 14.52 kgf/cm2. Keywords: Particle board, oil palm empty bunches, resin adhesive